Development of an Android Application for 3D Animation of Basic Silat Techniques in the Art of Self-Defence - Sham, Md Azani; Sabri, Muhamad Hakimi; Hamzah, Usuloudin; Zurina Yasak (Research and Innovation in Technical and Vocational Education and Training, 2023)
The rapid advancement of technology has had a significant impact on the field of education. One example is the utilization of Android-based mobile technology that harnesses multimedia as an effective tool to achieve learning objectives. This study aims to develop an Android application that combines 3D animation with the fundamental techniques of self-defence martial arts, specifically Silat, as an additional teaching resource for both teachers and students. The development of this application follows the ADDIE model, which consists of five main phases: analysis, design, development, implementation, and evaluation. Various software applications, such as Adobe Animate, Adobe Illustrator, Adobe Premiere Pro, and Blender, were employed to create this Android application. Six experts were selected to assess the application, including three content experts who are teachers involved in Silat co-curricular activities at secondary and primary school levels. The assessment instrument used was a checklist form designed specifically for expert evaluation. This form was utilized to assess the functionality of the Android application in terms of content, interaction, interface, and multimedia presentation design. The collected data was then analyzed and presented using frequency ratings and feedback notes. The findings from the data revealed that all three content experts agreed on the content design. Similarly, consensus was reached among the experts regarding the interaction design. However, differences of opinion emerged among them concerning the interface design and multimedia presentation, which require improvements from the developer. Overall, this Android application has been successfully developed and has undergone thorough testing. It can serve as a valuable guide for students to enhance their understanding of the subject matter.